PENERAPAN INTERPRETIVE STRUCTURAL MODELING (ISM) DALAM PENENTUAN ELEMEN PELAKU PENGELOLAAN TANAMAN TERPADU (PTT) PADI SAWAH MENUJU PERTANIAN BERKELANJUTAN DI KABUPATEN MERAUKE - Palobo, Fransiskus; Baliadi, Yuliantoro (Politeknik Negeri Lampung., 2019)
Program modeling in the application and determination of key actors in integrated cropland rice management and resource management for policy making is critical and strategic towards sustainable agriculture development. the objective of this research is to get key element actors in determining integrated crop management (PTT) of paddy rice for sustainable agriculture. As an indicator element interpretive structural modeling (ISM) in this research using 5 (five) Indicator element that is 1) Role of government, 2) Purpose, 3) Main obstacle, 4) Requirement of a program, 5) Institution involved. Results of interpretive structural modeling (ISM) analysis indicate that integrated rice plant cultivation to sustainable agriculture is the role of government in making strategic plan program hence need to follow by making technical instruction. Achieve the objective of applying integrated cropland rice management using high yielding varieties with high productivity and favored by farmers. The need for integrated cropland rice management needs to have proper fertilizer subsidies, seed subsidies, improved irrigation infrastructure and additional capital. The main constraint of integrated crop management is the uncertain climate change so pest disease is still high and at the time of planting season gadu water difficulty. While the institutions involved should be well synergized between the agricultural service and the institute for agricultural technology assessment. Policy direction in the strategic plan program needs a short, medium and long-term strategic plan by related institutions so that the youth will be evaluated according to the action stage.